1981
DOI: 10.1007/bf00782593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adaptation to sea water, 170% sea water and to fresh water on activities and subcellular distribution of branchial Na+?K+-ATPase, low- and high affinity Ca++-ATPase, and ouabain-insensitive ATPase inGillichthys mirabilis

Abstract: Iichthys rnirabilis after adaptation to salinities ranging from 170% SW to FW. Stabilities of these activities against freezing and deoxycholate solubilization and the temperature-dependence of activity rates were also investigated. Subcellular distribution and some kinetic properties of these activities, and of SDH were compared in branchial tissues of fish adapted to 170 % SW and to FW. 2. Na+-K+-ATPase was maximally active at a Na + concentration of 180 mM and K + concentration of 60 mM. This enzyme was lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Lasserre (1971) Lasserre & Gallis (1975) and Gallis & Bourdichon (1976) reported that Chelon lubrosus showed strongly increased gill Na+-K' ATPase activity in FW, with values twice those in SW, as we observed for M. cephalus juveniles, while results for Liza rumada were discordant. Furthermore, a high Na'-K' ATPase activity in FW has been reported in several marine euryhaline species (Kirschner 1968, Towle et al 1977, Doneen 1981, Stagg & Shuttleworth 1982. A reverse pattern has been observed in other species (De Renzis & Bornancin 1984).…”
Section: Discussionmentioning
confidence: 83%
“…Lasserre (1971) Lasserre & Gallis (1975) and Gallis & Bourdichon (1976) reported that Chelon lubrosus showed strongly increased gill Na+-K' ATPase activity in FW, with values twice those in SW, as we observed for M. cephalus juveniles, while results for Liza rumada were discordant. Furthermore, a high Na'-K' ATPase activity in FW has been reported in several marine euryhaline species (Kirschner 1968, Towle et al 1977, Doneen 1981, Stagg & Shuttleworth 1982. A reverse pattern has been observed in other species (De Renzis & Bornancin 1984).…”
Section: Discussionmentioning
confidence: 83%
“…[35][36][37] (6,38), although conflicting evidence exists (14). Perry (6)(7)(8)(9)(10)(11)(12), although the possibility of other active transport pathways has not been ruled out. Although the resent study does not address the mechanism(s) ofactive Ca + uptake, the methods used should prove useful in determining both the mechanism(s) and the regulation of Ca2`transport.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the "background" activities measured by for eels adapted to tap water (0.45 mM Ca 2 +) are comparable to the values obtained in the present study for ouabain insensitive activities in LCa group studied at the same Mg 2 + concentrations. Doneen (1981) observed a greater Mg 2 + ATPase activity in Gillichthys in FW than in fish adapted to 170% SW. The enzyme may play a physiological role in cellular homeostasis or in transferring Mg 2 + to the blood but if it is associated with the basolateral membrane of the CC the increase in activity may simply reflect an increase in the number of the CC in the gill.…”
Section: Effect Of Acclimation On Ouabain-insensitive Enzyme and A Tpmentioning
confidence: 90%
“…Fenwick (1979) reported that freshwater adapted eels had a higher Ca 2 + enzyme activity than seawater adapted fish. Doneen (1981) on the other hand did not observe any difference in the low affinity Ca 2 + ATPase between fresh and seawater Gillichthys. No changes were observed in the activity of the enzyme after transfer of fish from fresh to seawater (Ma 1976).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation